USO DE OBJETOS EDUCACIONAIS NO ENSINO DE CIÊNCIAS BIOLÓGICAS: ALTERNATIVA METODOLÓGICA PARA O ENSINO MÉDIO - Roberto Xavier, Antônio; Medeiros Olimpio, Danielly; Mota Neves de Almeida, Sinara; Simão Martins, Elcimar (LINKSCIENCEPLACE, 2026)
The idea of this research arose from concerns about the deficiency of material subsidies that support the teacher and the student, facilitating the interaction theory and practice and, consequently, the fixing of the contents and concepts of Biological Sciences in the teaching-learning of students of the 1st grade of High School in Schools, both located in the municipality of Redenção, state of Ceará. The main objective was to understand the main obstacles of the teaching of biological sciences in the 1st grade of the Redenção state education network in order to contribute with methodological proposals through the use of didactic-pedagogical form of educational objects as a tool to assist The teaching-learning process. Another intention was to demonstrate that, after the use of educational objects as a methodological proposal, teaching and fixing the contents of Biological Sciences become more attractive for the student, while providing a better assimilation of the contents of Biological Sciences and stimulating -o to become an active agent of the teaching-learning process.